Peran Pola Komunikasi Orang Tua dalam Membentuk Karakter Anak: Studi Kasus di Pondok Pesantren Daarul Muqorrobin Kota Tangerang - Aini Nur Ainiyah; Faisal Tomi Saputra; Riza Gusti Rahayu (Institut Nalanda, 2026)
This research aims to explore how parental communication patterns contribute to shaping children's character within an Islamic boarding school environment. The study focuses on students of Daarul Muqorrobin Islamic Boarding School in Tangerang City, who come from diverse family backgrounds and experience varying levels of communication with their parents. Using a qualitative approach and a case study method, data were collected through in-depth interviews, observation, and documentation involving students, parents, and pesantren staff. The Family Communication Patterns (FCP) theory serves as the theoretical framework, identifying family communication types such as consensual, pluralistic, protective, and laissez-faire. The findings reveal that an open and balanced communication pattern (consensual) between control and discussion is more effective in fostering disciplined, moral, and independent character development in students. In contrast, minimal or one-way communication tends to hinder the character-building process. This study offers significant implications for parents and pesantren administrators to establish synergistic communication in order to cultivate morally and spiritually strong future generations.